The Extractive Industries Transparency Initiative (EITI): A mine of information to be exploited? - Yannick Bouterige; Neerbewendé Rachid Pafadnam (Fondation pour les études et recherches sur le développement international (FERDI), 2024)
While two-thirds of African countries can be considered resource-rich, taxation of the extractive sector is a challenge for these countries, which also need revenues to finance their development. An in-depth analysis of mining and petroleum rent sharing is therefore essential but is hindered by difficulties in accessing the necessary economic and fiscal data. The wealth of information published by the Extractive Industries Transparency Initiative (EITI) is certainly a response to this need for data. However, despite their obvious interest, the use of EITI data is se- verely limited by their lack of centralization and their low level of comparability between countries and even between years. In this context, the construction of a real transnational and pluri-annual EITI database, harmonized and easily us- able, seems to be increasingly essential for providing all stakeholders with the information necessary to understand and analyze the African extractive sector.
Keywords: 330